Impact of climatic, demographic and disease control factors on the transmission dynamics of COVID-19 in large cities worldwide - Metelmann, S.; Pattni, K.; Brierley, L.; Cavalerie, Lisa; Caminade, C.; Blagrove, M.S.C.; Turner, J.; Sharkey, K.J.; Baylis, M. (Elsevier, 2021)
Approximately a year into the COVID-19 pandemic caused by the SARS-CoV-2 virus, many countries have seen additional “waves” of infections, especially in the temperate northern hemisphere. Other vulnerable regions, such as South Africa and several parts of South America have also seen cases rise, further impacting local economies and livelihoods. Despite substantial research efforts to date, it remains unresolved as to whether COVID-19 transmission has the same sensitivity to climate observed for other common respiratory viruses such as seasonal influenza. Here, we look for empirical evidence of seasonality using a robust estimation framework. For 359 large cities across the world, we estimated the basic reproduction number (R0) using logistic growth curves fitted to cumulative case data. We then assess evidence for association with climatic variables through ordinary least squares (OLS) regression. We find evidence of seasonality, with lower R0 within cities experiencing greater surface radiation (coefficient = −0.005, p < 0.001), after adjusting for city-level variation in demographic and disease control factors. Additionally, we find association between R0 and temperature during the early phase of the epidemic in China. However, climatic variables had much weaker explanatory power compared to socioeconomic and disease control factors. Rates of transmission and health burden of the continuing pandemic will be ultimately determined by population factors and disease control policies.